THE EFFECT OF COMPANY’S MANAGEMENT DISCUSSION AND ANALYSIS DISCLOSURE TO SHAREHOLDERS REACTION - Natasya Imanuella Soriton; Rinny Rantung (Klabat Accounting Review, 2021)
This research aims to describe how Indonesia capital market would react upon non-financial information Management Discusion and Analysis disclosure for 85 manufacturing company in 2018. The result of the research showed that (1) non-financial information for manufacturing companies such as Management Discussion and Analysis as part of annual report has no significant impact towards investor in Indonesia. (2) MD&A purpose for disclosing information in manufacturing company for Indonesia capital market is not functioning. (3) MD&A disclosure for manufacturing companies are not fully prepared by management. Keywords: Management discussion and analysis, market reaction, trading volume activity